Planning Pedestrian Paths for Trade and Service Areas of Balikpapan City with the Walkability Concept - Enggal Muluk Kumandang; Dwiana Novianti Tufail (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2022)
Corridor of the commercial area of Jalan MT. Haryono Balikpapan City specifically from the MT. Haryono Bridge to the Traffic Light Beruang Madu Monument has the characteristics of high mobility by motorized vehicles. Under these conditions, efforts are needed to encourage non-motorized movements. One of the efforts that have been made in the provision of pedestrian paths in the trade and service area. However, the lane has several problems, such as damaged sidewalks, motorized vehicles that often park around the sidewalks, and there are no guiding blocks for disabled users. Therefore, this study aims to plan a pedestrian path in the commercial area in the corridor of Jalan MT. Haryono uses the concept of walkability. This research uses walkability suitability analysis, community satisfaction level analysis, and Photo Mapping analysis. The results of the suitability analysis showed that segment 1 of the research area was not following the walkability and it was necessary to improve the pedestrian path infrastructure and add supporting facilities such as chairs, trash cans, CCTV, and shade plants, to guide blocks. While in segment 2, almost all of the variables are appropriate and require maintenance of several pedestrian path facilities. In the analysis of the level of community satisfaction using the Multicriteria Satisfaction Analysis, the planning priorities of the 4 walkability indicators are obtained. The results of this analysis show that segment 1 requires planning for the development of safety and comfort indicators, while segment 2 requires planning related to the development of safety and beauty indicators. The results of Photo Mapping show that it is necessary to add road barrier facilities, guiding blocks, parking ban signs, resting chairs, green lanes, repairing pedestrian lane infrastructure, and improving zebra crossing in segment 1. Segment 2 requires additional parking ban markers, speed bumps, chairs, trash cans, green paths, and care for weeds growing along the walkways